Pengaruh Inflasi, Kurs dan Tingkat Suku Bunga Terhadap Non Performing Loan Pada BPR Cabang Batam - Nurhidayah Dalimunthe; Viola Syukrina E. Janrosl (Peneliti.net, 2023)
This study aims to analyze the effect of inflation, exchange rates and interest rates on Non Performing Loans (NPL) at BPR Batam branch. The variables examined in this study are inflation, exchange rates and interest rates as independent variables while Non-Performing Loans (NPL) as the dependent variable. In this study, the methods used for data analysis were descriptive statistical tests, classical assumption tests, multiple linear regression analysis and hypothesis testing which were processed using the SPSS (Statistical Product and Service Solutions) version 25. The data used in this study were secondary data. namely the first quarter financial reports of Conventional BPR banks which are used as the research sample. The research sample is 28 conventional banks in the city of Batam which are registered with the Financial Services Authority for the 2018-2022 period with a saturation sampling technique as a sampling technique. The results of this study based on the T test obtained the results that partially inflation, exchange rates and interest rates had no significant effect on Non Performing Loans (NPL). Based on the results of the F test or simultaneously obtained results that inflation, exchange rates and interest rates have no significant effect on Non Performing Loans (NPL).